STRATEGI PENYUSUNAN PETA DAKWAH DALAM PERSPEKTIF ADMINISTRASI DAKWAH UNTUK MENINGKATKAN EFEKTIVITAS MANAJEMEN DAKWAH DALAM KONTEKS PENDIDIKAN ISLAM KONTEMPORER - Slamet Riyadi; Sugianto; Sahrulloh; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
This study examines the strategy for developing a da’wah mapping (peta dakwah) within the perspective of da’wah administration to enhance the effectiveness of contemporary da’wah management. The research is motivated by the need for more adaptive, data-driven, and strategic da’wah practices in response to rapid social and technological changes. Using a qualitative approach with a library research method, this study analyzes relevant literature on da’wah administration, management, and mapping. The findings reveal that da’wah mapping serves as a strategic instrument that integrates managerial functions, including planning, organizing, implementing, and controlling. Through systematic identification of community conditions covering social, economic, cultural, and religious aspects da’wah programs can be designed more accurately, efficiently, and contextually. Furthermore, da’wah mapping significantly contributes to improving targeting accuracy, optimizing resource utilization, and enhancing program quality. The integration of da’wah mapping with digital technology also supports a data-driven approach to da’wah, enabling broader outreach and more effective engagement with modern society. Therefore, the application of da’wah mapping is essential in developing effective, adaptive, and sustainable da’wah management in the contemporary era.